PENERAPAN ANGGARAN BERBASIS KINERJA SEBAGAI SALAH SATU SARANA MEWUJUDKAN GOOD GOVERNANCE PADA PEMERINTAH KABUPATEN LAHAT - Dewi Rina Komarawati (Program Studi Magister Manajemen FE Unsri, 2010)
The objectives of this research are (1) to know how far the Government of Lahat Residence applies the performance based budgeting as foundation in arrange the Income and Expense Budgeting, and (2) to know how performance based budgeting can materialize good governance in Lahat Residence.Research finding has shown that during period of years 2004-2008, the performance of the Government of Lahat Residence was increasing after applying performance based budgeting. Tax acceptance, as one of the source of residence income, was increasing years after years. Good governance which measure by the Increasing of Residence Income, the Effort Development, the Decrease of Unemployment Number, and Development of Gross Regional Domestic Product are was giving the positive result. The government of Lahat Residence have to keep action of perfecting in apply performance based budgeting so that they can get more result.Key Words : Performance Based Budgeting, Income and Expense Budgeting, and Good Governance.